VExUS: The Holy Grail or Achilles Heel of fluid management? - Karki, Bipin; Ghimire, Suson; Vaddi, Balaji; Shrestha, Gentle Sunder; Soliman-Aboumarie, Hatem (Journal of Nepalese Society of Critical Care Medicine, 2024)
Excessive use of intravenous fluids is becoming less favored in most critical case scenarios due to increased identification of adverse effects associated with fluid overload. Venous Excess Ultrasound (VExUS) is a recent point of care ultrasound (POCUS) tool in critical care. It has a promising utility to identify end point of resuscitation, onset of fluid congestion and to facilitate initiation of de-resuscitation. Whether or not significant association or causation exists between congestion as identified by VExUS and clinically relevant outcomes is yet to be observed as newer evidences surface and establish the place of VExUS in clinical practice. This narrative review aims to describe the current need to have a tool to accurately identify fluid overload, give a brief description of the physiology behind along with techniques of performing VExUS. We have also summarized the available evidences so far for and against VExUS and the limitations of this technique.